Development of dye affinity adsorbents for recovery of polyclonal anti-hepatitis B core antigen immunoglobulin G - Wongchuphan, Rattana (2010)
Antibodies such as immunoglobulin G (IgG) have been used extensively for therapeutic and diagnostic purposes. Protein A affinity chromatography which is highly specific towards IgG is a standard method to purify it. However, using expensive and unstable protein A in large-scale production has increased the antibody production cost accordingly. Affinity dye-ligands which are widely used for protein purification has demonstrated their high binding capacity as 40 mg/mL comparable to protein A. Moreover, their widespread availability, ease and speed of preparation, chemical stability, and ease of storage, render them an attractive alternative choice. Especially, their economy is also a major consideration in replacement of expensive protein A. Thus, the development of selective recovery of polyclonal anti-hepatitis B core antigen immunoglobulin G (anti-HBcAg IgG) from rabbit sera has been investigated. Four different reactive dye-ligands; Cibacron Blue 3GA (CB), Reactive Brown 10 (RB 10), Reactive Red 120 (RR 120) and Reactive Green 5 (RG 5) were covalently attached on the Streamline quartz base matrix via triazine linkage under alkali condition. Essentially at start, IgG antibody’s binding capacity screening of these immobilized dyes was required. Similar amount of dye-ligands attached on the bare matrix, determined by mass balance method was attributed relatively in comparison of adsorption capacities for different dye-ligands. From the simulating adsorption study in single protein system, the immobilized RG 5 was chosen as its capacity for fewer albumins and more IgG adsorbed at pH 7.0, compared to other immobilized dye-ligands possessing similar ligand density. The content of RG 5 immobilized on the matrix was 17.4 µmol/mL adsorbent. About 64% of rabbit IgG was bound on the immobilized RG 5 at pH 7.0 in binary protein binding system with similar ratio of both albumin and rabbit IgG. The maximum adsorption capacity (qm) of RG-5 immobilized adsorbent for rabbit IgG was 49.0 mg/mL adsorbent and the dissociation constant (Kd) value was found to be 3.33×10–6 M. The phenomenon of reversible IgG adsorption on the adsorbent appeared to follow the Langmuir-Freundlich isotherm model. Serum from the immunized rabbits against hepatitis B core antigen (HBcAg) was used as a feedstock containing polyclonal anti-HBcAg IgG solely for batch antibody purification study. Highly abundant albumin and other serum proteins which constitute about 80% of total serum protein are a major interference in dye-ligand affinity chromatographic studies. This leads to the strategy of removing contaminant proteins before subjecting to dye-ligand immobilized system. Anion exchange adsorbents like the Streamline DEAE and Streamline Q XL were introduced as their high capacity available for albumin. Although both anion exchangers were capable of removing most of albumin and other contaminants greater than 90%, the loss of IgG was higher in the presence of Q XL. As a result, the removal of albumin was accomplished in high efficiency via a strong adsorption on DEAE under optimized conditions as followed: 0.5 mg/mL initial protein concentration, pH 8.0; 0.25 mL settled bed volume of Streamline DEAE. Consequently, 80% of polyclonal anti-HBcAg IgG was recovered. A two step procedure using Streamline DEAE anion exchanger and RG-5 immobilized adsorbent was performed for removing albumin and capturing IgG, respectively, under the optimized conditions. After antibody adsorption, bound IgG was eluted in elution medium, pH 8.0 containing 1.0 M NaCl, resulting about 53% IgG recovered with 86% purity and a purification factor of 6. As exhibited in the current study, DEAE anion exchanger is credited for high efficacy to remove most contaminant proteins from rabbit serum. The purified antibodies can be a useful reagent in diagnosis of chronically infected hepatitis B carriers. Moreover, synthetic dye-ligands can be a potential alternative possessing a tendency of binding to biomolecules for several biological purposes.